Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.

Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Asymmetric N-heterocyclic carbene (NHC)-catalyzed annulation of modified enals with enolizable aldehydes - Yetra, Santhivardhana Reddy; Kaicharla, Trinadh; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
N-Heterocyclic carbene (NHC)-catalyzed highly enantioselective lactonization of modified enals with enolizable aldehydes, proceeding via the alpha,beta-unsaturated acylazolium intermediates, is reported. The reaction results in the asymmetric synthesis of synthetically important 4,5-disubstituted dihydropyranones.

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Asymmetric vinylogous michael reaction of cyclic enones with silyloxy furans - Jadhav, Amol P.; Rao, V. U. Bhaskara; Singh, Pradeep; Gonnade, Rajesh G.; Singh, Ravi P. (Chemical Communications, 2015)
The asymmetric vinylogous Michael reaction of cyclohexenone/medium and large cyclic enones with 2-silyloxyfuran is still a synthetic challenge. In this report, we have explored 1,4-conjugate addition of an enantioselective chiral, primary diamine catalyzed, 2-silyloxy furan to various cyclic enones and beta-substituted cyclic enones. The reaction provided syn-Michael adducts (cycloalkane connected gamma-butenolide) with good yields, diastereo and enantioselectivities. Furthermore, the synthetic potential of these syn-Michael adducts is demonstrated by 1,4-addition of nucleophiles on the butenolide substructure.

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Application of roof-shape amines as chiral solvating agents for discrimination of optically active acids by NMR spectroscopy: study of match-mismatch effect and crystal structure of the diastereomeric salts - Gupta, Riddhi; Gonnade, Rajesh G.; Bedekar, Ashutosh V. (Journal of Organic Chemistry, 2016)
Optically active roof-shape amines were prepared and scanned as chiral solvating agents to study molecular recognition of acids by NMR analysis. Three types of amines were studied to establish a match mismatch effect for structurally diverse acid analytes. Single-crystal X-ray diffraction analysis was performed on the diastereomeric salts of roof shape amines and both isomers of mandelic acid to establish molecular conformation and correlate the absolute configuration with the observed NMR shift. The present system also recognizes the two isomers of weakly acidic BINOL and its derivatives.

Aryne [2,3] stevens rearrangement - Roy, Tony; Thangaraj, Manikandan; Kaicharla, Trinadh; Kamath, Rupa V.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
Arynes are employed in the transition-metal-free and mild [2,3] Stevens rearrangement of tertiary allylic amines for the synthesis of functionalized homoallylic amines in moderate to good yield with a broad substrate scope. The key nitrogen ylide intermediate was generated by the N-arylation of allyl amines using arynes. Moreover, the reaction of chiral allyl amines with arynes resulted in the enantiospecific synthesis of homoallylic amines. In addition, preliminary studies on the [1,2] Stevens rearrangement is also presented.

Au(I)/Ag(I) co-operative catalysis: interception of Ag-bound carbocations with α-gold(I) enals in the imino-alkyne cyclizations with N-allenamides - Bagle, Pradip N.; Mane, Manoj V.; Vanka, Kumar; Shinde, Dinesh R.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2016)

AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron

Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus

Access to a variety of Ge(II) and Sn(II) compounds through substitution of hypersilyl moiety - Bisai, Milan Kumar; Ajithkumar, V. S.; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
We have prepared amidinato-germylene (3) and -stannylene (4) with a tris(trimethylsilyl)silyl substituent and subsequently substituted the hypersilyl moiety by reacting 3 with chlorophosphines, which led to phosphino germylenes (5 and 6) with concomitant liberation of (Me3Si)(3)SiCl. Exploiting the fluoride affinity of the silicon atom, we have prepared pentafluoropyridyl germylene (7) and -stannylene (8) by reacting 3 and 4 with C5F5N with simultaneous elimination of (Me3Si)(3)SiF. These are the first examples of aryl germylenes or stannylenes prepared via C-F bond activation of a perfluoroarene. The reaction of 4 with Me3NO resulted in a novel Sn2O2 ring (9). All compounds were characterized by single-crystal X-ray structure determination studies.

Access to enantiomeric organic compounds with potential for synthesis via racemic conglomerates: inositol derivatives as a case in point - Patil, Nivedita T.; Patil, Madhuri T.; Sarkar, Nitai; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2021)
The crystal structure database was used to identify inositol derivatives that could be crystallizing as racemic conglomerates. Among the six racemic inositol derivatives identified, racemic 4-O-tosyl-6-O-benzyl-myo-inositol-1,3,5-orthoformate (A) was found to be a true conglomerate and was resolved on the multigram scale by the preferential crystallization technique. This resolution procedure does not require the use of any enantiomeric resolving agent. The resolved enantiomers of A are useful for the synthesis of natural and unnatural enantiomeric derivatives of inositol, since they carry orthogonal hydroxy protecting groups. Racemic 4-O-methanesulfonyl-myo-inositol-1,3,5-orthoformate (B) on crystallization from common organic solvents generally yielded racemic twin crystals, while in the presence of structural analogs as additives, they yielded true racemic crystals. A comparison of the crystal structures of the true racemate, twinned crystal and crystal of one of the enantiomers of B, revealed the reasons for the formation of polymorphic (twin) crystals. Such instances are relatively rarely encountered but nevertheless shed light on our understanding of polymorphism and twinning of crystals.

Achiral and chiral NNN-pincer nickel complexes with oxazolinyl backbones: application in transfer hydrogenation of ketones - Jagtap, Rahul A.; Ankade, Shidheshwar B.; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2021)
We describe the synthesis of new NNN-oxazolinyl-pincer nickel complexes and their application in the transfer hydrogenation of ketones. Achiral NNN-ligands, R `(2)-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [((R ` 2-OxNNNEt2))-H; R' = H (3a), R ` = Me (3b)], and chiral ligands, (R)-R `-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [(R)-((R `-OxNNNEt2))-H; R ` = Ph (3c), R ` = CH2Ph (3d), R ` = Pr-i (3e), R ` = (CH2Pr)-Pr-i (3f)], were efficiently synthesized. Treatment of these ligands with (DME)NiCl2 afforded the desired amido-pincer nickel complexes, ((R ` 2-OxNNNEt2))NiCl [R ` = H (4a), R ` = Me (4b)] and ((R `-OxNNNEt2))NiCl [R ` = Ph (4c), R ` = CH2Ph (4d), R ` = Pr-i (4e), R ` = (CH2Pr)-Pr-i (4f)], in good yields. All the ligand precursors and nickel complexes were thoroughly characterized by various analytical techniques. The molecular structures of 4a, 4d and 4f were established by X-ray crystallography. The developed nickel complexes were found to be efficient catalysts for the transfer hydrogenation of ketones using (PrOH)-Pr-i as a viable hydrogen source. Enantioselectivity in hydrogenation was not observed with the developed chiral catalysts.

Acid mediated sulfonylation of para-quinone methides with tosylmethyl isocyanides for the synthesis of diarylmethyl sulfones - Kumar, Pawan; Kale, Someshwar B.; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2021)
An efficient, hydrochloric acid promoted reaction for the synthesis of diarylmethyl sulfones has been developed via unprecedented 1, 6-conjugate addition reaction of tosylmethyl isocyanide (TosMIC) with para-quinone methides.This catalyst free reaction provides various diarylmethyl sulfones in good to excellent yields in an operationally simple method under metal free conditions. Further transformations of the productsare also demonstrated.
Keywords: 1; 6-Conjugate addition; aromatization; Diarylmethylsulfone; para-Quinonemethide; TosMIC

Accelerated Rauhut-Currier dimerization enabled the synthesis of (+/-)-incarvilleatone and anticancer studies - Kotammagari, Tharun K.; Misra, Sweta; Paul, Sayantan; Kunte, Sunita; Gonnade, Rajesh G.; Santra, Manas K.; Bhattacharya, Asish K. (Beilstein Journal of Organic Chemistry, 2023)
The total synthesis of racemic incarvilleatone has been achieved by utilizing unexplored accelerated Rauhut-Currier (RC) dimeriza-tion. The other key steps of the synthesis are oxa-Michael and aldol reactions in a tandem sequence. Racemic incarvilleatone was separated by chiral HPLC and the configuration of each enantiomer was determined by single-crystal X-ray analysis. In addition, a one-pot synthesis of (+/-)-incarviditone has been achieved from rac-rengyolone by using KHMDS as a base. We have also assessed the anticancer activity of all the synthesized compounds in breast cancer cells nonetheless, they exhibited very limited growth suppression activity.
Keywords: dimerization; incarviditone; incarvilleatone; oxa-Michael; Rauhut-Currier

Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product